LAWS OF SYNTHESIS OF SILICA GELS WITH MOLECULAR-SIEVE PROPERTIES - Коsеnко Olena І. (Proceedings of National Aviation University, 2010)
Influence of conditions at all stages of silica gel synthesis on the formation of structure with molecular-sieve properties was investigated. It was shown that the conditions promoting formation of such structure, are: the minimum rate of the reaction of silicon acid gel polycondensation, minimum duration of recondensation processes, maximum value of capillary compression forces at drying and constant dehydration speed.